Effect of ionic liquid bmimno3 to chitosan-starch blend biopolymer electrolyte system - Shaffie A.H.; Misenan M.S.M.; Isa M.I.N.; Khiar A.S.A. (Trans Tech Publications Ltd, 2024)
Indexed by Scopus/ERA